Educator's guide to searching the internet - Treadwell, Mark (SkyLight, 1998)
Surf the Net with confidence and ease. This teacher-friendly guide gives you all the tools you need to use the Internet to its full potential in the classroom. It demystifies the use of semantic fields and boolean searching to help you choose the best search engine for your needs.